Relationship between Chlamydia Trachomatis infection, infertility, and serum 25-hydroxyvitamin D: a cross-sectional study from NHANES 2013-2016 - Miran Na; Lin Zeng; Xiya Sun; Yinrou Huang; Mingmei Lin; Xu Zhi (BMC, 2024)
Abstract Background Chlamydia trachomatis is a common sexually transmitted disease that is associated with considerable morbidity and harmful sequelae, including pelvic inflammatory disease and infertility. Strategies for prevention and treatment of infertility in women with C. trachomatis infection require further investigation. There is evidence suggesting that vitamin D could be a potential treatment. This study aimed to investigate the relationship between serum 25-hydroxyvitamin D [25(OH)D] levels, chlamydia seropositivity, and the risk of infertility in women. Methods We conducted this cross-sectional study using 2013-2016 National Health and Nutrition Examination Survey data. Women aged 18-39 years with complete serum 25(OH)D and chlamydia Pgp3Ab multiplex bead/enzyme-linked immunosorbent assay data available were included. The correlation between 25(OH)D level, chlamydia seropositivity, and infertility was evaluated using the weighted chi-squared test and the t-test with multivariate logistic regression and moderation effect models. Results Among the 1424 women who met our eligibility criteria, the weighted chlamydia seropositivity rate was 36.8%. The 25(OH)D level was significantly lower in the seropositive group compared with seronegative control. (P = 0.009). After adjusting for ethnicity, the effect of 25(OH)D was no longer significant (P = 0.693). Further analysis in the chlamydia-seropositive subset revealed that the vitamin D level was lower in the infertile group (P = 0.024). In an interaction model, 25(OH)D was found to antagonizes the positive relationship between chlamydia and infertility (OR = 0.985, 95% CI: 0.971-0.999, P = 0.040). Conclusion The serum vitamin D level may be more related to the prognosis in terms of infertility than to the risk of chlamydia infection. This finding may reveal a possible treatment strategy for chlamydia infection.